Management of Severe Preeclampsia with Anemia in Pregnant Women with Covid-19 Infection : A Multidisciplinary Approach - Handayani, Ririn; Anggraeni, Ernawati; Sari, Melati Puspita; Handayani, Yuni; Cahyono, Hendra Dwi (Indonesian Socety of Obstetrics and Gynecology, 2025)
Coronavirus disease 2019 (COVID-19) is a disease that is currently pandemic almost worldwide, with the first case in Indonesia on March 2, 2020, spreading rapidly across the entire country. Pregnant women are a vulnerable group to experience health disorders, especially infectious diseases, due to changes in physiological body and immune response mechanisms within their bodies. In this study, we report a case of COVID-19 in a 31-year-old pregnant woman at 30-31 weeks of gestation, who is pregnant with her second child and complained of leaking amniotic fluid and shortness of breath. Physical examination results showed: positive SARS-CoV-2 antigen swab test, BP 156/112 mmHg, T (36.0°C), heart rate 107 beats per minute, respiratory rate 30 breaths per minute, fetal heart rate 144 beats per minute, SpO2 97%, urine protein +4, Hb 4.4 g%. Vaginal toucher examination revealed cervical dilation of 1 cm, negative for amniotic fluid leakage, and cephalic presentation. Spontaneous delivery process. The baby was born normally, female, APGAR score 1-2, weight 900 grams, length 27 cm, positive anus. Complications accompanying pneumonia, metabolic acidosis, anemia, melena, coagulopathy. This case report contains clinical descriptions, diagnosis, and management of care for pregnant women with Covid-19.